Traditional Marriage in Lombok: A Study of the Acculturation of Hindu and Islamic Cultures on the Meaning of Begawe Merariq for the Muslim Sasak Community of Lombok - Saprudin Saprudin (UIN Sunan Gunung Djati, 2025)
The purpose of this research is basically to provide a clear picture of the acculturation of Hindu and Islamic culture occurring in the tradition of begawe merariq (traditional elopement ceremony) in the Islamic Sasak Lombok community, as well as the typology of the Sasak people in interpreting begawe merariq, because there is a lot of Hindu cultural acculturation. In this research, the author uses a qualitative approach that emphasizes the importance of developing and compiling theories that are always rooted in inductive-empirical thinking. Regarding data collection techniques, participant observation, interviews, and secondary data searches were used. The begawe merariq culture is a tradition that has been passed down and preserved because at this time the people of Lombok can gather and stay in touch with each other. Apart from being a family reunion, it is also a momentum to build the bond of an extended family (kadangjari, semeton jari). However, the meaning of kadangjari is now starting to be less understood, lived, and implemented because it is eroded by the insistence of materialism, individualism. Regarding the acculturation of Hindu culture in the Sasak community, the majority is not related to the main teachings of Islam, but is only seen in matters of customs that are Furu'iyah. It also applies only to some Sasak people who still use old traditions, while others carry out begawe in a modern way.